2020
DOI: 10.1037/xap0000274
|View full text |Cite
|
Sign up to set email alerts
|

Seeing isn’t necessarily believing: Misleading contextual information influences perceptual-cognitive bias in radiologists.

Abstract: A substantial number of medical errors in radiology are attributed to failures of perception or decision making, although it is believed that experience (or expertise) might buffer diagnosticians from some types of perceptual-cognitive bias. We examined how the quality of contextual information influences decision making and how underlying perceptual-cognitive processes change as a function of experience and diagnostic accuracy. Twenty-one radiologists dictated their findings on 16 deidentified musculoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Eye‐tracking studies evaluated the frequency of these different error types in musculoskeletal radiographs and chest radiographs. Fawver et al (2020) found that most errors in musculoskeletal radiographs are decision‐making errors. The evaluation of chest radiographs showed similar results with some variability, with most errors being decision‐making errors followed by recognition errors and detection errors (Donovan & Litchfield, 2013; Kundel et al, 1978; Manning et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Eye‐tracking studies evaluated the frequency of these different error types in musculoskeletal radiographs and chest radiographs. Fawver et al (2020) found that most errors in musculoskeletal radiographs are decision‐making errors. The evaluation of chest radiographs showed similar results with some variability, with most errors being decision‐making errors followed by recognition errors and detection errors (Donovan & Litchfield, 2013; Kundel et al, 1978; Manning et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As thoracic splenosis is rare and presents as multiple pleural-based nodules in the left hemithorax. It could possibly mislead the radiologist and even the physician in charge, especially if important information's are missing [10] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Commonly known cognitive biases both inside and outside of healthcare include the anchoring bias, ascertainment bias, availability bias, confirmation bias, ordering effect, outcome bias, optimistic bias, and overconfidence bias (Elstein, 1999 ; Smith, 2017 ; Vahabi, 2007 ). Commonly utilized cognitive biases among both patients and medical providers (Fawyer et al, 2020 ; Braverman & Blumenthal, 2012 ; Hershberger et al, 1997 ) include the sunk-cost principle, the loss/gain framing bias, and the omission bias. These commonly used cognitive biases negatively affect both probability estimation of health-related risk behaviors and synthesis of health information.…”
Section: Cognitive Biasmentioning
confidence: 99%